Hierarchically structured VO2@PPy core-shell nanowire arrays grown on carbon nanotube fibers as advanced cathodes for high-performance wearable asymmetric supercapacitors. (November 2018) - Man, Ping; Zhang, Qichong; Sun, Juan; Guo, Jiabin; Wang, Xiaona; Zhou, Zhenyu; He, Bing; Li, Qiulong; Xie, Liyan; Zhao, Jingxin; Li, Chaowei; Li, Qingwen; et al.
Abstract: Fiber-shaped asymmetric supercapacitors (FASCs) have emerged as intriguing energy storage devices for next-generation wearable electronics. However, the limited specific capacitances that arise from electrode materials severely restrict further enhancement of their energy densities. We successfully fabricated a hierarchically structured three-dimensional VO2 @polypyrrole (VO2 @PPy) core-shell nanowire array (NWA) on carbon nanotube fiber (CNTF) via a facile and cost-effective route. Such a composite structure not only enables a highly pseudo-capacitive VO2 core to provide a large surface area for reversible Faradic redox reactions, but also uses a highly conductive PPy shell to suppress the dissolution of VO2, thus making the hybrid fiber a new state of fibrous electrode with exceptional specific capacitance and rate behavior. To benefit from these superior features, we assembled a high-performance FASC with an operating voltage of 1.8 V and achieved a remarkable specific capacitance of 60.6 F/cm 3 and an extraordinary energy density up to 29.3 mWh/cm 3 at a current density of 0.25 A/cm 3 . In addition, the FASC device exhibited excellent flexibility; its capacitance retention remained at 88.9% after bending 4000 times. Thus, these findings should help to develop advanced VO2 -based cathodes for next-generation wearable energy storage devices. Graphical abstract: Image 1